Indigenous self-determination in cryospheric science: The Inuit-led Sikumik Qaujimajjuti (“tools to know how the ice is”) program in Inuit Nunangat, Canada - Beaulieu, L.; Arreak, A.; Holwell, R.; Dicker, S.; Qamanirq, O.; Moorman, L.; Wilson, K.; Segal, R.; Crichton, S.; Bell, T. (Frontiers in Earth Science, 2023)
Inuit have lived along the shoreline of the frozen Arctic Ocean for centuries. Our wellbeing, culture, and identity are closely tied to safe and dependable ice access. As the ice becomes more unpredictable with a changing climate, Elders and experienced ice users recognize that their accumulated wisdom and experience of safe ice travel—their Inuit Qaujimajatuqangit (IQ; a term used to describe Inuit knowledge and values) of sea-ice—must be shared and applied in new ways for the benefit of younger generations. Here we illustrate one such application that enables young Inuit scientists to learn and apply the tools and skills they need to create operational community-scale sea-ice maps (Sikumik Qaujimajjuti, or “tool to know how the ice is”). Our cross-cultural partnership approach—called the Sikumiut-SmartICE model—focuses on developing the skills of young Inuit to create the maps, while non-Indigenous partners provide mentorship, tools, and training. Our novel maps incorporate culturally relevant ice terminology, on-ice monitoring data and observations, and IQ-grounded interpretations of ice features and travel conditions from near-real time optical and radar satellite imagery. The layers of data are integrated into a local GIS, enabling the creation of maps that reflect local and seasonal travel patterns and meet our information needs in information content, extent and frequency. The maps are posted and shared through social media platforms preferred by the community. The maps are a trusted source of travel information because they are made by one of our own, using local language, experience, and IQ. The Sikumik Qaujimajjuti program illustrates the incredible potential of Indigenous self-determination in cryospheric science when the scientific merit of IQ is fully recognized, when Indigenous researchers are able to access technologies and training to apply their IQ, and when non-Indigenous partners mentor and support young Indigenous scientists.